Psikhologiya sporta v institute na ulitse Kazakova - Rodionov, A. V.; Hudatov, N. A. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The purpose of this publication was to consider the main landmarks of the sports psychology`s development in the All-Russian Research Institute of Physical Culture and Sport. The authors show the outstanding role of such psychologists as S. G. Gellershtein, V. A. Alatortsev, L. D. Gissen, A. V. Alexeyev, in the development of Russian sports psychology.